Galactose to tagatose isomerization at moderate temperatures with high conversion and productivity - Josef R. Bober (Nature Portfolio, 2019)
Production of tagatose, a sugar substitute, by isomerization of galactose suffers from unfavorable enzymatic kinetics, low enzyme stability, and low equilibrium constant. Here, the authors simultaneously overcome these limitations by encapsulating l-arabinose isomerase in permeabilized Lactobacillus plantarum.